On Becoming a District of Choice: Implications for Equity Along the United States–Mexico Border. (October 2019) - Kotok, Stephen; Knight, David S.; Jabbar, Huriya; Rivera, Luis E.; Rincones, Rodolfo
Purpose: Despite the popularity of open enrollment as a school choice mechanism, there is little research on how principals behave in a district-run competitive setting. This study adds to our understanding of how open enrollment policies affect the role of the principal as well as educational equity by examining the roles and behaviors of school principals in an unregulated marketplace of schools.Research Method: This study uses an explanatory sequential mixed methods approach. We first analyze school-level transfer data for school year 2014-2015 and demographic data in order to examine trends such as poverty concentration as well as to identify "winners, " "losers, " and "nonplayers" in the open enrollment marketplace. Since principals are heavily involved in recruitment, student screening, and selection of specialized programs, we interviewed 12 principals to better understand their role in the competitive settings.Findings: We find that some schools have emerged as "winners" in this marketplace, attracting large numbers of transfers without losing many students, while other principals and schools struggle to overcome a negative perception and find a market niche to attract students. Our quantitative analysis indicates a relatively small relationship between open enrollment and increased segregation in the district. District oversight seems to have prevented worsening segregation. However, many principals seek more control on the screening process raising equity concerns if formal regulations are not provided.Implications: These findings have implications for school and district leaders navigating open enrollment plans as a means to increase enrollments and encourage innovation while also maintaining equity.